2012
DOI: 10.7314/apjcp.2012.13.8.3741
|View full text |Cite
|
Sign up to set email alerts
|

Bicluster and Pathway Enrichment Analysis of HCV-induced Cirrhosis and Hepatocellular Carcinoma

Abstract: Background: Hepatocellular carcinoma (HCC) is the sixth most common cancer worldwide and the most common form of liver cancer. However, while it is associated frequently with hepatitis C virus (HCV) there is only an elementary understanding of its molecular pathogenesis. Methods: To gain insight into the molecular mechanisms of HCV-induced hepatocarcinogenesis, we performed microarray analysis on 75 surgical liver samples from 48 HCV-infected patients. Results: There were 395 differentially expressed geness be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…HCV infection is well known globally as one of the main risk factor in HCC development even if evidence for its causal role in hepatocarcinogenesis is a little more recent [ 33 , 34 ]. The rate of HCC progression varies greatly among patients with chronic HCV infection and this is probably due to the existence of a complex interplay between host, viral and environmental factors [ 35 ], including older age, male gender, alcohol intake and HCV infection [ 36 - 38 ].…”
Section: Chronic Hcv Infectionmentioning
confidence: 99%
“…HCV infection is well known globally as one of the main risk factor in HCC development even if evidence for its causal role in hepatocarcinogenesis is a little more recent [ 33 , 34 ]. The rate of HCC progression varies greatly among patients with chronic HCV infection and this is probably due to the existence of a complex interplay between host, viral and environmental factors [ 35 ], including older age, male gender, alcohol intake and HCV infection [ 36 - 38 ].…”
Section: Chronic Hcv Infectionmentioning
confidence: 99%
“…Alcohol drinking was responsible for 15.7% with smoking responsible for 13.9% (Fan et al, 2013). The differentially expressed genes study between cirrhosis and HCC samples showed the upregulating of ECM-receptor interaction, focal adhesion, cell adhesion molecules and other cancer-related pathways, and downregulating of complement and coagulation cascades pathways involved in HCV-induced hepatocarcinogenesis (Cheng, et al, 2012). They also found a significant hypermethylation of tumor suppressor genes (P14, P15, and P73), and a mismatch repair gene (O6MGMT) in HCV related chronic liver disease and HCC.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, with a population of more than 80 million, Egypt is considered to have the highest prevalence of hepatitis C in the world and consequently a high frequency of hepatocellular carcinoma (HCC) (Zekri et al, 2012;2013). It was shown that, approximately 30% of infected individuals clear the viral infection naturally while 70% develop chronic disease that may finally lead to liver cirrhosis (LC) and/or hepatocellular carcinoma (HCC) (Morgan, 2011;Cheng et al, 2012). Several immunological factors are implicated in the determination of disease outcome in HCV infected patients including the adaptive immune response and the innate immune system, which regulate disease progression in those patients (Rehermann, 2009;Zekri et al, 2010).…”
Section: Introductionmentioning
confidence: 99%